Natural convection heat transfer in Gambrel roofs - Varol, Yasin; Koca, Ahmet; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2007)
Buoyancy induced natural convection is investigated with a numerical technique in Gambrel roofs. The geometry adapted to both winter day conditions, the bottom is hot temperature while top is cold, and summer day conditions, bottom is cold and inclined top wall is hot temperature. Governing equations in streamfunction-vorticity form are solved with finite difference technique and algebraic equations are solved using successive under relaxation (SUR) method. Rayleigh number is taken as parameter which affects the flow and heat transfer. Its value changes between 10(3) and 10(7). It is found that winterlike boundary conditions are more effective than summerlike boundary conditions on the flow field and heat transfer in the roof. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: natural convection; Gambrel roof; heat transfer